DOES THE LISBON TREATY MAKE PROGRESS FOR THE DEVELOPMENT OF A COMMON EUROPEAN ENERGY POLICY? - Jakštas, Tadas (Politologija, 2015)
There has been an endless discussion among policy makers about the need to have a common energy policy within the Community of European states. The EU energy policy has always been governed by a sort of go-it-alone principles. There has been a lack of common approach to energy problems and no real determination to create a common energy market. As a result, the 2006and 2009 gas disputes between Russia and Ukraine left certain Central and South European countries without gas and showed how vulnerable the EU is when it does not have real instruments to react unanimously. In that context the effects of Lisbon Treaty in energy security sector are very important to assess by looking what contribution the Treaty makes in that field. Moreover, it could be argued that The Lisbon Treaty established the main priorities of the European energy policy and has envisaged the possibility for the EU to play a more active role in that sector. Furthermore, new article on the issue of energy provides a guideline for the EU of how to govern their energy policies: ensure the functioning of the energy market, ensure security of energy supply in the Union, promote energy efficiency and interconnection of energy networks. In addition, the extension of co-decision and qualified majority voting in energy policy area provides member states a better opportunity to discuss issues, accommodate interests and strike for a broad consensus in energy policy area. Even more importantly, the Treaty speaks about “a spirit of solidarity” if severe difficulties of supply arise. However, taking into account the individual policies that states tend to implement in order to enhance their energy security levels (e.g. German and Russia cooperation in the project of NordStream, Italian ENI and Gazprom cooperation in various energy projects in Siberia, Royal Dutch/Shell and Lukoil collaboration) the question then may be raised – what are the real outcomes envisaged in the Treaty of Lisbon? Does it give the real instruments for implementing policies beyond words? Does it provide a possibility to transcend relative gains, i.e. to transcend national interests in order to create pan European response?